KOMUNIKASI DAKWAH DENGAN QOULAN MASYSURA DI INSTAGRAM NU ONLINE JAWA TIMUR (@nuonlinejatim): Kajian Feminisme dalam Kacamata Islam - Marzuqi, Muhammad Ganda; Faizatul Mukarromah; Ilham Maulana Yusup; Moh. Ali Aziz (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2024)
The gender issue in Indonesia remains a major concern to this day, especially among women's activists who advocate for the importance of gender equality. Efforts to achieve this equality have been carried out through women's empowerment, which is done through various training and seminars on gender. Da'wah communication has six principles, one of which is Qaulan Maysura (words that are easy to understand) as mentioned in Surah Al-Isra’ verse 28. The live broadcast of the lecture titled